Finding the Best Model in Nonlinear Regression: Using the Coefficient of Determination - Vitri Aprilla Handayani; Widya Reza; Saba Mehmood (Jurnal Varian, 2023)
In Indonesia, inflation plays a significant role in shaping economic growth. Therefore, it is essential to examine the impact of inflation on economic growth through a comprehensive analysis. This analysis aims to identify the factors influencing economic growth in Indonesia by utilizing nonlinear regression analysis. The study focuses specifically on modeling economic growth in Batam City and its correlation with inflation. The primary goal is to identify the most effective nonlinear regression model that accurately represents the relationship between economic growth and inflation, as determined by the coefficient of determination. The method used in this research is nonlinear regression methods provide a more accurate and comprehensive analysis when dealing with complex relationships and can help uncover valuable insights that may be missed by simpler linear models. The results of the analysis finding the model that is suitable for modeling inflation on economic growth is a quadratic model with a coefficient of determination of 73.4%. The research has found that the best model for explaining the impact of inflation on economic growth is the Quadratic model with an R-value of 0.734 or 75%. These results indicate that the Quadratic model can account for 75% of the influence of inflation on economic growth.